1991
DOI: 10.1084/jem.174.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD2 antibodies induce T cell unresponsiveness in vivo.

Abstract: The CD2 receptor functions as an adhesion and signal molecule in T cell recognition. Multimeric binding of CD2 on T cells to its physiologic ligand LFA-3 on cognate partner cells in vitro efficiently augments the antigen-specific T cell signal delivered by the T cell receptor/CD3 complex. The precise contribution of the antigen-nonspecific CD2-LFA-3 interactions to T cell immune responses in vivo, however, has been difficult to assess. Here we analyzed the role of CD2 in the murine immune response using a nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 53 publications
6
48
0
Order By: Relevance
“…In addition to providing costimulatory signals that promote T cell activation and B cell differentiation (23,24), signaling through CD2 has complex immunosuppressive effects both in vitro and in vivo (25,26,95,96). Treatment of mice with anti-CD2 prevents the onset of autoimmune diabetes mellitus and allergic experimental encephalomyelitis (97,98).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing costimulatory signals that promote T cell activation and B cell differentiation (23,24), signaling through CD2 has complex immunosuppressive effects both in vitro and in vivo (25,26,95,96). Treatment of mice with anti-CD2 prevents the onset of autoimmune diabetes mellitus and allergic experimental encephalomyelitis (97,98).…”
Section: Discussionmentioning
confidence: 99%
“…However, anti-CD2 monoclonal antibodies (MAb) also have inhibitory effects on T cell function both in vitro (25) and in vivo (26) 60 years), and the mean disease duration was 6 years (range 0-30 years). The study group included 6 hospitalized individuals with newly diagnosed, untreated SLE; the remainder were ambulatory and were receiving prednisone, nonsteroidal antiinflammatory drugs, or hydroxychloroquine, but not cytotoxic drugs.…”
Section: Decreased T Cell Response To Anti-cd2 In Systemic Lupus Erytmentioning
confidence: 99%
“…As for mice lacking ICAM-1, the e¡ect is more pronounced when low-a¤nity binding peptides are used. The polyclonal T-cell hyporesponsiveness that persists long after membrane CD2 recovery follows incubation with antibodies suggests that some anti-CD2 mAbs also deliver an inhibitory signal (Guckel et al 1991). It is interesting to note that the blockade of CD2 and LFA-1 co-stimulation pathways could result in a T-cell anergy state mimicking that described following blockade of CD28 or B7 activation (Bell & Imboden 1995).…”
Section: Targeting Lfa-1 and Cd2 Molecules (A) Inhibition Of Lfa-1^icmentioning
confidence: 99%
“…The cytoplasmic domain of CD5 has an immunoreceptor tyrosine-based inhibition motif (ITIM) and has been shown to negatively regulate signaling through both the TCR and BCR [27,29]. In vitro and in vivo studies with anti-CD2 antibodies revealed inhibition of T cell function, including longlasting hyporesponsiveness, that could not be entirely explained simply by blockade of CD2 interactions with its ligand [30,31]. Thus, both CD2 and CD5 appear capable of antagonizing T cell activation, whereas in contrast, CD28 has only been reported to augment mature T cell activation.…”
Section: Discussionmentioning
confidence: 99%